The use of social media in different phases of the new product development process: a systematic literature review - Runyue Han; Julia Brennecke; Dhruba Borah; Hugo K. S. Lam (R&D Management, 2024)
Using social media is high on the list of priorities for many firms looking to enhance their innovation performance in the different phases of the new product development (NPD) process. Mirroring this rising practical importance of using social media for NPD, scholars have presented a diverse range of perspectives and underscored the need for a systematic literature review. Accordingly, this study reviews 110 papers from 2002 to 2023, to synthesize the use of social media across three phases: discovery, development, and launch. Our analysis identifies nine NPD objectives that social media addresses and discusses challenges encountered. Building on this analysis, we develop an organizing framework to guide practitioners on how to adopt social media to achieve better NPD performance and propose directions for future research.
Keywords: 330